Efektifitas media sosial dalam meningkatkan partisipasi peserta pelatihan di BBPVP Medan - Putri Amanda; Nursapia Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the effectiveness of Instagram as a social media platform in increasing participant engagement in training programs at the Medan Center for Vocational Training and Productivity (BBPVP), as well as to identify the inhibiting factors. The method used is a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The research informants consist of public relations staff, social media administrators, training participants, and members of the public who use social media. The results show that Instagram plays an effective role as a public communication medium in increasing participant engagement through the presentation of attractive visual content, clear information, and interactive features that encourage audience involvement. This effectiveness is reflected in the increased awareness, interest, and registration actions of training participants. However, the effectiveness has not yet been optimal due to several obstacles, such as limited human resources, lack of consistency in content publication, and low levels of interaction among certain segments of the audience. The conclusion of this study indicates that social media has great potential to enhance participation in training programs if supported by well-planned digital communication strategies, relevant content, and professional management.